Influence of pH-cycling in de-remineralization environment on the strength degradation of orthodontic elastics - França, Gabriela Martins; Lima, Max José Pimenta; Rodrigues, Rebeka Bahia; Campos, Elisângela de Jesus; Santamaria Junior, Milton (Brazilian Dental Science, 2026)
Objective: Factors related to the elastic composition and oral conditions may influence the strength in its decomposition during orthodontic treatment. This study aimed to evaluate the effect of pH on the force degradation of orthodontic elastics. Material and Methods: A total of 180 elastics were analyzed, comprising 90 Morelli elastics (Group A) and 90 American Orthodontics elastics (Group B), each stretched to an initial extension of 15 mm. Samples were divided into six subgroups (n=30) based on the immersion medium: distilled water (control), pH 5.0 solution (acidic), and solutions with pH 4.3 and pH 7.0 (de-remineralizing), which were refreshed daily. The strength evaluation was performed at the hours 0, 24, 48, 72 and 96. The strength was measured by a digital dynamometer to evaluate its degradation. Results: Force degradation of the elastics occurred over time in all immersion media, including distilled water. In Group A, after 48 hours, elastics immersed in the acidic pH solution exhibited greater force degradation compared to those in the de-remineralizing solution (p < 0.05). In Group B, the degradation was greater in the de-remineralization solution within 48 hours. Conclusion: All elastics exhibited progressive force degradation, which varied with pH and material brand. Acidic conditions increased force loss in Morelli elastics, while de-remineralizing conditions had greater impact on American Orthodontics elastics. KEYWORDS De-remineralization environment; Elastomers; Hydrogen ion concentration; pH-cycling; Orthodontics.